The rise of Africa's digital economy The European Investment Bank's activities to support Africa's transition to a digital economy - European Investment Bank (European Investment Bank, 2021)
The rise of an African digital economy is improving millions of lives and rapidly transforming societies. Africa has a unique opportunity to become more sustainable and create economic growth through the better use of data, instead of using old technologies that consume fossil fuels. Digitalisation has many benefits: It speeds up the spread of information, brings people closer together, creates jobs and makes societies more efficient. Digitalisation is a key part of the European Union's work in Africa. The European Commission and the African Union say digital technology is a priority for economic and social development in Africa. The European Investment Bank will keep playing a central role in Africa's future by providing targeted digital expertise and finance to the public and private sectors.